PENGARUH FREE CASH FLOW DAN KEPEMILIKAN MANAJERIAL TERHADAP KEBIJAKAN HUTANG (Studi Kasus pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Uli Budi Yanti S; Ratih Kusumastuti (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research aims to find out 1}. Is there a partial influence of free cash flow on debt policy in food and beverage sub-sector companies listed on the IDX for the 2018-2021 period? 2}. Is there a partial influence of managerial ownership on debt policy in food and beverage sub-sector companies listed on the IDX for the 2018-2021 period? 3}. Is there a simultaneous influence of free cash flow and managerial ownership on debt policy in food and beverage sub-sector companies listed on the IDX for the 2018-2021 period? 4}. How big is the influence of free cash flow and managerial ownership on debt policy in food and beverage sub-sector companies listed on the IDX for the 2018-2021 period? The data analysis technique uses multiple linear regression which is logged with the help of statistical software version 22. Source data sourced from IDX financial report data on the IDX website (www.idx.co.id). Based on the results of this research, it shows that there is an influence of Free Cash Flow on Debt Policy in Food and Beverage Sub-Sector Companies Listed on the IDX for the 2018-2021 period. This is proven by tcount>ttable (-2.059>2.080). There is no influence of Managerial Ownership on Debt Policy in Food and Mint Sub-Sector Companies Registered on BEI for the 2018-2021 Period. where seen from the tcount value, it is smaller than ttable, namely (-2.608<-2.080) with a significance level of 0.016<2.080. Simultaneously, Free Cash Flow and Managerial Ownership influence Debt Policy in Food and Beverage Sub-Sector Companies Listed on the IDX for the 2018-2021 period. This is proven by Fcount > Ftable 4.401 > 3.47